Clinical Supervisors’ Views on Strengthening Theory-Practice Coherence — A Sociology of Knowledge Perspective - Højbjerg, Karin; Bromann Bukhave, Elise; Sand Nielsen, Cathrine; Engelsen, Søren; Lehn, Sine (Professions and professionalism, 2024)
Increased focus on the practical components of Danish health care education and greater coherence between theory and practice have been persistently identified as major issues requiring quality improvement. Policy initiatives to standardize education in eight health professional bachelor’s programs, including greater theory-practice coherence, prompted us to explore the types of educational practices highlighted by clinical supervisors to strengthen coherence between theory and practice. Thirty-one qualitative interviews were conducted with clinical supervisors in nursing, physiotherapy, occupational therapy, nutrition and health programs, biomedical laboratory science, midwifery, radiography, and psychomotor therapy. Data were thematically analyzed in a sociology of knowledge framework. We found that theoretical knowledge had a higher status in the programs. The imbalance may have negative consequences, whereby theoria activities in the practical part of the programs may, in unintended and subtle ways, increase in dominance. The intrinsic qualities of clinical practice are, therefore, at risk of being downplayed.